IMPROVING THE MECHANISM OF BANK LENDING IN THE CONTEXT OF REGULATING FINANCIAL AND ECONOMIC IMBALANCES IN UKRAINE (World of finance, 2021)
Introduction. A notable structural challenge of Ukraine's national economy compared to economically developed countries is the numerous financial and economic imbalances, low institutional and market capacity of the business environment, whose contribution to GDP, national product and value added, exports and employment is critically low. This leads to a weakening of the middle class, reduced business activity, economic independence of the territories and deepening economic imbalances in the country.The purpose of the article of paper is to substantiate effective bank lending instruments in the focus of regulating financial and economic imbalances in Ukraine.Results. It is proved that transformations in the business environment of the country, slow pace of structural changes in the national economy, imbalance in the labour market, low level of commercialization of scientific developments and lack of innovative strategies for industrial development, as well as loss of capital due to economic (market) deviations and implementation of special instruments to stimulate bank lending, in particular in terms of regulating economic imbalances in Ukraine. It was found that the most effective mechanisms are credit-infrastructure, market-product, organizational-security, project-transformation. The author's approach to positioning mechanisms for stimulating the development of bank lending in terms of regulating financial and economic imbalances (a systemic measures for regulating the sectoral balance of the national economy; structural superstructure to ensure a high level of competitive environment in all sectors of the economy, as the main driver of socio-economic development and scientific and technical progress, an effective measures for intensifying the pace of systemic transformation and restructuring of industrial and economic complexes of the national economy).Perspectives. The subject of further research is to study the impact of the banking sector on economic deviations as factors in the strengthening of financial and economic imbalances in the country.